MINAT MEMBACA MAHASISWA PENDIDIKAN JASMANI DI PERPUSTAKAAN JURUSAN ILMU KEOLAHRAGAAN - Siti Purnama Sari; Andika Triansyah; Eka Supriatna (Universitas Tanjungpura, 2019)
AbstractThis study is aimed to determine reading interest and the factors influencing the interest in reading on the Physical Education students of Tanjungpura University Pontianak. This Survey research was conducted with quantitative descriptive method. 250 students from the 3rd, 5th, and 7th semesters were taken as the population. 130 of the population were taken as the sample by applying a simple random sampling technique. Direct observation was implemented as the data collection technique as well as the questionnaire was used as the instrument of data collection. Based on the data calculation, the percentages were obtained based on 130 student answers on the 25 questions of questionnaire with the answer categorized as very high by 6,92% with 9 students, high by 26,92% with 35 students, moderate by 43,85% with 57 students, low by 16,16% with 21 students, and very low by 16,15% with 8 students. The average of the overall categories is 81,71, categorized as high. Keywords: Library, Reading Interest, Sports Science.